HUBUNGAN PENGETAHUAN TENTANG PERSONAL HYGIENE DAN PEMANFAATAN FASILITAS SANITASI LINGKUNGAN DENGAN KEJADIAN PENYAKIT INFEKSI KULIT PADA PONDOK PESANTREN ANSHOR AL-SUNNAH AIR TIRIS - Gustrianda, Etri (Universitas Pahlawan, 2022)
The prevalence of skin infections in developing countries is around 6,569 cases (89.75%), while in Indonesia the incidence of skin infections is 4,362 cases (68.43%), while in Riau Province the prevalence of skin infections is around 4,385 cases. Personal hygiene is personal cleanliness and health which aims to prevent the emergence of disease in oneself and others. Skin disease is an infection of microorganisms on the skin caused by the presence of germs, bacteria, viruses, parasites and fungi. The aim of the research is to determine the relationship between knowledge about personal hygiene and the use of environmental sanitation facilities and the incidence of skin infections at the Anshor Al-Sunnah Air Tiris Islamic Boarding School. Quantitative research design with a cross sectional design, this research was carried out on 10-15 October 2021 at the Anshor Al-Sunnah Air Tiris Islamic Boarding School. The population in this study was students in grades 8 and 9 MTS and 11 and 12 MA, totaling 568 people. The sample in this study amounted to 235 people. The sample technique used is Simple Random Sampling. The instrument used is a questionnaire. The data obtained were analyzed using the chi square test, the significance level was 95%. The results of the research show that there is a significant relationship between knowledge about personal hygiene of respondents and the incidence of skin infections Pvalue 0.002 (p?0.05), indicating that there is a significant relationship between the use of environmental sanitation facilities and the incidence of skin infections Pvalue 0.000 (p?0.05). The Anshor Al-Sunnah Islamic Boarding School is expected to provide further information about personal hygiene and skin infections, so that students know the importance of personal hygiene and so that skin infections do not occur again.